AN ANALYSIS OF BOUNDED RATIONALITY IN JUDICIAL LITIGATIONS: THE CASE WITH LOSS/DISAPPOINTMENT AVERSE PLAINTIFFS - LANGLAIS, Eric (Journal of Advanced Research in Law and Economics; Vol 1 No 1 (2010): JARLE Volume I Issue 1(1) Summer 2010, 2016)
For psychologists, bounded rationality reflects the presence of cognitive dissonance and/or inconsistency, revealing that people use heuristics (Tversky, and Kahneman 1974) rather than sophisticated processes for the assessment of their beliefs. Recent research analyzing litigations and pretrial negotiations also focused on boundedly rational litigants (Bar-Gill 2005; Farmer, and Peccorino 2002) relying on a naïve modelling of the self-serving bias. Our paper in contrast introduces the case for disappointment averse litigants, relying on the axiomatic of Gull (1991). We show that this leads to a richer analysis in comparative statics; at the same time, this proves to be … disappointing: for the purposes of public policies in favour of the access to justice, recommendations are quite ambiguous.
Keywords: conflicts, litigation, negotiation, disappointment aversion